An Exploration on the Scope of the Subject Responsibility of Rural Old-age Security in China - Lan, Peilin (International Journal of Social Sciences and Public Administration, 2024)
In our country, the aging of rural population, economic development, urbanization rate and population flow, the miniaturization of rural families has become a general trend, and the traditional family pension mode no longer ADAPTS to the rural pension security, the government and the market intervention is the inevitable choice facing the grim situation of rural aging.As the main responsibility of rural old-age security, the government, families, individuals and the market play a vital role in jointly guaranteeing the life of farmers for the aged. Making clear the responsibility scope of government, family, individual and market in rural old-age security can maximize rural old-age welfare to the greatest extent.